MENGENAL PRINSIP BUNYI PADA INSTRUMEN ANGKLUNG - Rena Amalika Asyari; Dyah Murwaningrum (POLITEKNIK PIKSI GANESHA, 2018)
Sound is not visual form, it will be more difficult when we used in text concept only. The aim of this research is to simplify the laws of sound by the traditional angklung. This research discusses about teaching method. Students invited to analyzing, reasoning, and trying how the laws of sound working on instrument. So the students can be understand and apply the law of sound to daily activity.The research used descriptive - analytical methods by describing the parts of angklung and analyzing the laws of sound in sound production. The results of this research are formulas to teach based on practice. Students will understand about the laws of sound simply.